Carbon dynamics in slash and burn systems and land use alternatives: findings of the alternative to slash and burn programme - Woomer, P. L. (1998)
Trabajo presentado en el Workshop on Carbon Pools and Dynamics of Tropical Ecosystems, Belem, Brazil. Del 1 al 5 de diciembre, 1997.